Toward a political economy of the commons : simple rules for sustainability /: simple rules for sustainability. (2022) - Cai, Meina; Murtazashvili, Ilia, 1975-; Murtazashvili, Jennifer Brick; Salahodjaev, Raufhon
No abstract available